2019
DOI: 10.3390/atmos11010025
|View full text |Cite
|
Sign up to set email alerts
|

Coupling of Soil Moisture and Air Temperature from Multiyear Data During 1980–2013 over China

Abstract: Soil moisture is an important parameter in land surface processes, which can control the surface energy and water budgets and thus affect the air temperature. Studying the coupling between soil moisture and air temperature is of vital importance for forecasting climate change. This study evaluates this coupling over China from 1980–2013 by using an energy-based diagnostic method, which represents the momentum, heat, and water conservation equations in the atmosphere, while the contributions of soil moisture ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Within land-atmosphere interactions, soil moisture anomalies have been identified by many studies to play a key role by its control of the surface fluxes [1]. Additionally, existing studies have demonstrated the impact of soil moisture anomalies on extreme events such as heatwaves [2], floods [3] and droughts [4], as well as its importance in operational services and climate monitoring [5,6] at both regional and global scales. While they demonstrate the significant role of soil moisture, most of these studies rely on model simulations for which large uncertainties remain unexplored, thus, observations are necessary to understand the impact of soil moisture better.…”
Section: Introductionmentioning
confidence: 99%
“…Within land-atmosphere interactions, soil moisture anomalies have been identified by many studies to play a key role by its control of the surface fluxes [1]. Additionally, existing studies have demonstrated the impact of soil moisture anomalies on extreme events such as heatwaves [2], floods [3] and droughts [4], as well as its importance in operational services and climate monitoring [5,6] at both regional and global scales. While they demonstrate the significant role of soil moisture, most of these studies rely on model simulations for which large uncertainties remain unexplored, thus, observations are necessary to understand the impact of soil moisture better.…”
Section: Introductionmentioning
confidence: 99%
“…The climate signal during spring (March, April, and May) was used as a predictor to forecast the summer rainfall in sub-regions of the Poyang Lake Basin. In the land-atmosphere coupling domain, similar approaches have been widely used with a potential time-lag as a forecast indicator [42]. The 130-item climate index dataset was obtained by averaging the March, April, and May values of each index from the database, which provided a wide range of choices for selecting a potential index as a forecast indicator of Poyang Lake basin sub-regional precipitation variation.…”
Section: Datamentioning
confidence: 99%
“…Recently, Gao et al (2018) found that the LLH is s a hot spot of land-atmosphere coupling over eastern China in spring. Additionally, the LLH is also a relatively strong SM-SAT coupling region in China during spring (Yuan et al, 2020). However, to what extent SM affects SAT in the LLH during spring and its possible mechanisms are yet to be studied, which are the main purpose of this research.…”
Section: Introductionmentioning
confidence: 99%